Karl Popper’s Falsification In Implementation Management Chain Green Supply - Rizqi, MN; Khomsiyah, Khomsiyah (Jurnal HARMONI: Jurnal Akuntansi dan Keuangan, 2025)
Research This aim For analyze How draft Karl Popper’s falsification can implemented in implementation management chain supply green. The method used is a literature study and content analysis. The results of the research obtained that Implementation paradigm Karl Popper’s falsification in GSCM provides framework strong work​ For ensure that initiative green based on evidence empirical that can tested. Research conceptual about falsification in GSCM opens opportunity big For study empirical continued.